Factors Affecting the Learning Outcomes of College Students during Online Class - Sajirun, Aljumar Abdulla; Falcasantos, Child Panes; Abrasaldo, Dianne Sael; Rebollos, Ian Carl Faustino; Villahermosa, Juliemae Ufana; Bondiogan, Jefferson; Acosta, Queennie Rubi; Handang, Juspher Gamorez (Jurnal Pendidikan Progresif, 2022)
Factors affecting the Learning Outcomes of College Students during Online Class. Objective: The purpose of this study was to determine the factors affecting the achievement of learning outcomes of college students during online class and to know how they cope with the shift to online class to achieve learning outcomes. Methods: The study employed qualitative method that focused in the identifying and analyzing what all the respondents’ experiences do have common factors in the context of the phenomenon. With this, the data was gathered through an interview of five (5) 3rd year and 4th year students of Western Mindanao State University who were taking Bachelor of Elementary Education and enrolled in online classes during the academic year 2021-2022.  Findings: The study found out several factors experienced by the students that affected their learning outcomes during online class which can be summarized as internet connectivity, physiological factors, non-academic influences, technological satisfaction and learning environmental. Conclusion: Based on the result, it clearly shows that online learning has significant issues that need further investigations. It can be assumed that the sudden shift of classes to an online mode of learning is less effective than the face-to-face set-up. Various issues were disclosed and these factors can be subdued by adjusting oneself into this mode of education.  Keywords: learning outcomes, online class, college students.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202212